A Multidisciplinary Approach to Biopsychosocial Care for Adults With Inflammatory Bowel Disease: A Pilot Study. Issue 12 (15th June 2018) - Lee, Chang Kyun; Melmed, Gil Y; Mann, Amy; Danovitch, Itai; Hedrick, Rebecca; McGovern, Dermot P B; Targan, Stephan; Shih, David; Vasiliauskas, Eric; IsHak, Waguih William; Feldman, Edward
Abstract: Background: This study reports on the logistics and feasibility of a novel multidisciplinary approach to biopsychosocial care at a tertiary adult inflammatory bowel disease (IBD) center. Methods: Consecutive patients referred for a new IBD consultation completed the following self-assessments: the Short Form-12, the Patient Reported Outcome Measurement Information System (PROMIS) Global Health Scale, the World Health Organization Disability Assessment Schedule 2.0, and the PROMIS-29. These measures were scored at the time of appointment check-in by a trained licensed clinical social worker (SW), and those scoring 1.5 standard deviations below the population mean were targeted for SW assessment and intervention at the point of care; patients or providers could also request a SW evaluation even if cutoffs were not met. In this stepped-care model, the SW could refer to same-day on-site psychiatry services or outside interventions and services. In addition, we implemented a 12-month curriculum with a monthly didactic and case-based education seminar for health care providers who interact with patients with IBD. Results: Between February 2014 and May 2015, 110 patients (53% male; mean age, 42 years) completed a self-assessment. All patients completed their self-assessment within 10 minutes. Of these, 36.4% (40/110) were targeted for SW assessment and intervention. The SW interventions were grouped into 4 categories: psychological education and coping tools for symptom management and emotional wellness (n = 30); psychotherapy referrals (n = 30); financial/governmental programs (n = 11); and psychiatry referrals for consultation and/or medication prescription (n = 21). The educational seminars were highly rated by participating providers. Conclusions: A multidisciplinary biopsychosocial approach to adult IBD care is feasible. Education for providers and close coordination across specialties are critical to the success of a multidisciplinary biopsychosocial program.